Developmental differences of kinematic and muscular activation patterns in instep soccer kick - Cerrah, A. O.; Simsek, D.; Soylu, A. R.; Ertan, H.; Nunome, H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of the study was to evaluate kinematic and muscular activation differences amongst different age groups of soccer players. Thirty male youth soccer players were divided into 3 groups according to their age (age 12-13; age 14-15; age 16-17). There were significant differences in ball velocities and isokinetic strength values amongst groups. Angular and linear velocities of hip, knee, ankle and toe were also significantly different (p<0.05) amongst groups in different phases. Furthermore, there were significant differences amongst groups regarding EMG activity of m. rectus femoris (RF), m. vastus medialis (VM), m. biceps femoris (BF) (p<0.05). From these results, it was suggested that that the ball velocity of in-step kicking increased with age that reflects the development of both muscular strength and coordination of kicking leg.